THE EFFECTIVENESS OF RENALOF® COMPARED TO KALKURENAL® AND PLACEBO - Kristyantoro, Benny; Alif, Sabilal; Djojodimedjo, Tarmono; Budiono, Budiono (Indonesian Urological Association, 2012)
Objective: To compare the effectiveness after administration of Renalof to Kalkurenal and placebo in patient with renal calculus. Material & Method: We analyzed 30 patient with renal calculi less than or equal to 20 mm (2 cm) between January 2011 and March 2011. Patients were divided into 3 groups. Nine patients were treated with placebo, 8 patients were treated with Kalkurenal and the last 13 patients were treated with Renalof. After 30 days, we analyzed calcium and uric acid excretion for 24 hours and measured the stone with plain abdominal film and renal ultrasound. Results: There were decreased in excretion of calcium and uric acid all of patients but not significant statistically (p > 0,05) and there were significant decreased on stone measurement in patient treated with Renalof. Conclusion: Renalof  can be given as adjunct therapy for patient with renal calculi. Keywords: Calcium and uric acid excretion in urine 24 hours, stone measurement and stone surface area.